Historical Trends in Graduate Research and Training of Diplomates of the American Board of Forensic Anthropology1. Issue 1 (25th November 2016) - Bethard, Jonathan D.
Abstract: The history of forensic anthropology has been documented by numerous scholars. These contributions have described the work of early pioneers in the field and have described important milestones, such as the founding of the Physical Anthropology Section of the American Academy of Forensic Sciences (AAFS) in 1972 and the American Board of Forensic Anthropology (ABFA) in 1977. This paper contributes to the growing literature on the history of forensic anthropology by documenting the academic training of all individuals who have been granted diplomate status by the ABFA ( n = 115). Doctoral dissertation titles were queried to discern broad patterns of research foci. A total of 39 doctoral granting institutions have trained diplomates and 77.3% of board‐certified forensic anthropologists wrote dissertations involving skeletal biology, bioarchaeology, or forensic anthropology. Board‐certified forensic anthropologists are a broadly trained group of professionals with far‐reaching anthropological interests and expertise.